MR angiography of the persistent trigeminal artery associated with an aneurysm - (:unkn) unknown (Turkish Neurosurgical Society, 1997)
This report presents a case of persistent trigeminal artery (PTA) associated with an ipsilateral ICA aneurysm demonstrated by MRA, and DSA. The aneurysm of the ipsilateral ICA located at the origin of posterior communicating artery has a direct physiopathological cause-result relationship with the PTA, unlike the previously reported cases of PTA.
Keywords: Aneurysm; MR angiography; Persistent trigeminal artery